Basic Statistical Tools for Improving Quality - Kang, Chang W. (Chang Wok), 1957-; Kvam, Paul H., 1962- (Hoboken, New Jersey : Wiley, 2011)
"This book is an introductory book on improving the quality of a process or a system, primarily through the technique of statistical process control (SPC). There are numerous technical manuals available for SPC, but this book differs in two ways: (1) the basic tools of SPC are introduced in a no-nonsense, simple, non-math manner, and (2) the methods can be learned and practiced in an uncomplicated fashion using free software (eZ SPC 2.0), which is available to all readers online as a downloadable product. The book explains QC7 Tools, control charts, and statistical analysis including basic design of experiments. Theoretical explanations of the analytical methods are avoided; instead, results are interpreted through the use of the software"--
Includes bibliographical references and index.
Keywords: Process control -- Statistical methods; Quality control -- Statistical methods